Pourquoi (et comment) faut-il corriger le montant des intérêts nominaux payés par les entreprises de la dépréciation de leur dette, afin de parvenir à une évaluation correcte du coût du capital ? - Laurent Cordonnier; Thomas Dallery; Vincent Duwicquet; Jordan Melmiès; Franck Van de Velde (Revue de la Régulation)
In previous publications, we developed an indicator dedicated to measure the cost and the over-cost of financial capital, which consists in: i) the real weight of financial incomes paid by corporations compared to their effort of productive investment (cost of capital) ; ii) the share of this cost which can be attributed to a pure rent (the over-cost of capital). This indicator and the calculations conducted to arrive at it have received some criticisms. The main one is that we would have proceed in our indicator to an unjustified deflation of paid interests. So as to compute the real charge that interests make weigh on corporations, we actually applied a real interest rate to corporations' debt. This operation, according to our critics, is useless, and even amounts to the same thing as deflate twice the level of paid interests, since the denominator of our indicator is itself in current prices. In this article, we try to convince that we were right to proceed this way, and that it doesn't consist in a deflation operation. In reality, it's about the taking into consideration of the reductions linked to debt depreciation when inflation is around. As we will show, taking into account these reductions in the calculation of the cost of capital amounts to the same thing as applying a real interest rate to debts.